Pizza ice cream with salami sprinkles: an analysis of the creativity of nominal compounding in multilinguals - Treffers-Daller, Jeanine; Ngee Thai, Yap; Majid, Sheikha (SAGE Publications, 2026)
Aims: This study aims to provide new insights into the creativity of nominal compounds in multilinguals. We ask whether mixed and unmixed compounds in Malay-English language contact follow Malay or English rules for the headedness of compounds and how pluralisation rules are applied to compounds across both languages. We also ask whether any innovative forms qualify as examples of rule-governed or rule-changing creativity. Design/Methodology/Approach: We analyse data from the existing literature on compounding in Malay and English, as well as data from a corpus of over a thousand utterances with intrasentential code-switching, collected by Majid (2019) among teachers of English in Malaysia. Data and Analysis: A qualitative analysis is made of the headedness of different nominal compounds and of the way in which these are pluralised. Findings/Conclusions: We found that Malay compounds in the data were generally left-headed and English compounds right-headed, but the directionality of mixed compounds depended largely on the language of the clause in which they appear: in Malaysian English short stories and newspapers, mixed compounds were right-headed, while they were left-headed in Malay clauses in the speech of teachers. Originality: The study brings together insights from the literature on creativity and insights from studies on nominal compounding. As in most studies of compounds, the constructions are studied in isolation, the current study is novel in that the language of the clause in which the compounds appear is also analysed. Finally, we bring together insights from the study of compounding in children as well as young adults, showing that the data from young adults are more likely to lead to rule-changing creativity. Significance/Implications: The study makes a contribution to our understanding of the ways in which language contact affects variability in compounding and can provide new insights into the separability of grammars in language contact.